2016
DOI: 10.5001/omj.2016.10
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Health Literacy, Self-efficacy, and Outcome Expectations on Adherence to Self-care Behaviors in Iranians with Type 2 Diabetes

Abstract: This study revealed that the potential impact of self-efficacy, outcome expectations, communicative, and critical HL should be considered in the education program for patients with diabetes. We found self-efficacy to be the most important predictor of diabetes self-care. Therefore, the use of self-efficacy theory when designing patient education interventions could enhance diabetes self-care. It is essential that health care providers assess patient's HL levels to tailor health-related information specific to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
101
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(118 citation statements)
references
References 25 publications
9
101
1
7
Order By: Relevance
“…Better psoriasis knowledge, measured by the PKQ, was strongly correlated with higher HL in seven of the HLQ scales and predicted a relevant R 2 change in all HL scales. Similar results have been found in research investigating a variety of disease conditions . Previous studies in psoriasis have demonstrated knowledge gaps concerning treatment and self‐management, but the relationships to HL are not yet addressed.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Better psoriasis knowledge, measured by the PKQ, was strongly correlated with higher HL in seven of the HLQ scales and predicted a relevant R 2 change in all HL scales. Similar results have been found in research investigating a variety of disease conditions . Previous studies in psoriasis have demonstrated knowledge gaps concerning treatment and self‐management, but the relationships to HL are not yet addressed.…”
Section: Discussionsupporting
confidence: 83%
“…Importantly one study that found self‐efficacy to be the most important predictor of diabetes self‐care also found that although HL was positively associated with self‐efficacy, and self‐efficacy was positively associated with self‐care behaviours, the correlation between HL and self‐care behaviours was statistically insignificant. These results indicate that HL may be a possible antecedent to self‐efficacy and that the influence of HL on self‐care behaviours may be mediated through self‐efficacy . This possible association needs more research.…”
Section: Discussionmentioning
confidence: 78%
“…Some studies have empirically found health literacy to be directly associated with diabetes self‐care behaviors (Cavanaugh et al., ; Kim, Yang, & Lee, ; Reisi et al., ), whereas others failed to detect any such direct association (Bohanny et al., ; Eyüboğlu & Schulz, ; Yamashita & Kart, ). These inconsistent results were addressed by Fransen et al.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the relationships between self‐efficacy and health literacy, and their effects on self‐care behaviors and glycemic control. Gao et al .…”
Section: Discussionmentioning
confidence: 99%